Natural Compounds as Anti-Arthritic Agents-A Review. - Sharma, Kiran; Rani, Ramya; Dhalwal, Kamlesh; Shinde, Vaibhav; Mahadik, K. R. (Pharmacognosy Reviews)
The last few years of arthritis researches in India have seen marked advances in our understanding of the basic treatments involved in the connective tissue disease and give a data of certain unexplored anti-arthritic herbs of Indian origin. These discoveries carried in the search for the paramount therapy which will prove to be inexpensive with minimal side effects. In more recent years, herbal treatment has risen to the forefront with the discovery of few Indian natural products which can generate better way for the treatment one of the major concerns of society, rheumatoid and the osteoarthritis. Various treatment modalities has been prescribed, along with the conventional and non-conventional medicine but due to their one or more adverse effects and dissatisfaction amongst users, these treatments are not satisfactory enough to give relief to the arthritic patients. So there has been rise in the use of CAM (complementary and alternative medicine) as compared to the allopathic system of medicine. Now a days, people from all parts of society have started to rely on the herbal therapy and formulations for arthritis. So, this review sparks some important Indian medicinal plants and herbs which benefit in any form of conditions associated with arthritis with special emphasis on rheumatoid arthritis and osteoarthritis.
Keywords: Rheumatoid arthritis (RA); Osteoarthritis (OA); Anti-Arthritic (AA); Complementary and Alternative Medicine (CAM); Anti-Inflammatory (AI); Gouty Arthritis (GA)